2015
DOI: 10.1177/0194599814563513
|View full text |Cite
|
Sign up to set email alerts
|

The Decline of Tracheotomy among Otolaryngologists

Abstract: This study illustrates that otolaryngologists at our institution are performing fewer tracheotomies over time. If this trend continues, the experience of our trainees may become diluted through reduction in surgical volume. While multi-institutional studies are warranted, this review provides a summary of data collected at a tertiary care institution, which may reflect national trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…The challenges of resident work‐hour restrictions, low case volumes, and pressure for increased operating room efficiency limit learning opportunities for surgical trainees in the operating room 2–4 . Although we previously demonstrated that the live porcine model has high face and content validity as a training tool for tracheostomy and LTR, use of animals for training can be limited due to anatomical differences from humans, cost, availability, ethics, a need for specialized facilities and personnel, and a limited ability to archive specimens or preserve progress 5,7,8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges of resident work‐hour restrictions, low case volumes, and pressure for increased operating room efficiency limit learning opportunities for surgical trainees in the operating room 2–4 . Although we previously demonstrated that the live porcine model has high face and content validity as a training tool for tracheostomy and LTR, use of animals for training can be limited due to anatomical differences from humans, cost, availability, ethics, a need for specialized facilities and personnel, and a limited ability to archive specimens or preserve progress 5,7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…The graft is commonly harvested from costal cartilage in older children and adolescents, and thyroid cartilage in neonates. Challenges of resident work‐hour restrictions, low case volumes, and pressure for increased operating room efficiency limit opportunities for surgical trainees to learn these procedures in the operating room 2‐4 …”
Section: Introductionmentioning
confidence: 99%
“…The safety, efficiency, and cost-effectiveness of percutaneous tracheostomy have been increasingly documented by surgeons, critical care physicians, and interventional pulmonologists, who now perform a majority of the procedures 384748…”
Section: Discussionmentioning
confidence: 99%
“…The safety, efficiency, and cost-effectiveness of percutaneous tracheostomy have been increasingly documented by surgeons, critical care physicians, and interventional pulmonologists, who now perform a majority of the procedures. 38,47,48 Tracheostomy abetted by Seldinger guide-wire insertion has inarguably enhanced the status of medicine and surgery in general and the repair of craniofacial and maxillofacial injury in particular, in the 21st century.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheostomy and open‐airway surgery are complex, low‐frequency procedures that require advanced training. Challenges of resident work‐hour restrictions and low case volumes limit learning opportunities for surgical trainees in the operating room . Surgical simulation is a growing area of research, as it can provide valuable opportunities for residents and fellows to learn and refine technical skills without risk to patient safety.…”
Section: Introductionmentioning
confidence: 99%